Agro‐ecology, resource endowment and indigenous knowledge interactions modulate soil fertility in mixed farming systems in Central and Western Ethiopia. (26th February 2021) - Agumas, Birhanu; Balume, Isaac; Musyoki, Mary K.; Benz, Martin; Nziguheba, Generose; Marohn, Carsten; Vanlauwe, Bernard; Cadisch, Georg; Rasche, Frank
Abstract: Site‐specific soil fertility management requires a fundamental understanding of factors that modulate soil fertility variability in the local context. To verify this assumption, this study hypothesized that soil fertility variability across two regions in Central and Western Ethiopia is determined by inter‐related effects of agro‐ecological zones and farmers' resource endowment ('wealthy' versus 'poor' farmers). Mid‐infrared spectroscopy coupled to partial least squares regression (midDRIFTS‐PLSR) and wet‐laboratory analyses were used to assess the soil fertility (soil pH, total soil carbon [TC] and nitrogen [TN], plant‐available phosphorous [Pav ] and potassium [Kav ]) across four agro‐ecological zones: 'High‐Dega' (HD), 'Dega' (D), 'Weina‐Dega' (WD) and 'Kola' (K). MidDRIFTS peak area analysis of spectral frequencies (2, 930 [aliphatic C‐H], 1, 620 [aromatic C = C], 1, 159 [C‐O poly‐alcoholic and ether groups] cm ‐1 ) was applied to characterize soil organic carbon (SOC) quality and to calculate the SOC stability index (1, 620:2, 930). Higher TC in HD, as well as higher TN and Kav contents in K were found in fields of wealthy compared with poor farmers. Resource endowment dependent soil fertility management options revealed SOC of higher quality in wealthy compared with poor farms in D. Agro‐ecological zones distinctions contributed to these soil fertility differences. Farmers distinguished visually fertile and less fertile fields based on soil colour. Higher pH in K and WD as well as Pav in K and HD were found in fertile (brown/black) than less fertile (red) soils. To conclude, tailor‐made soil fertility management in the local context must consider agro‐ecological zones and resource endowment interactions along with farmers' indigenous knowledge.